The Baldrige Criteria for Public Organisations - USA : Improvement Guide. - Tuominen, Kari. (Excellence Frameworks - Baldrige Series, 2013)
A self assessment workbook that has been drawn up as a self-assessment tool for organisations in the public sector and central and local government.The book explores the relationships between strategies, processes and results and gains a better understanding of the impact of change and the need for renewal and continuous improvement.The page presents examples, events, sayings and anecdotes, so that the reader can understand the reasons and consequences without explanation. The books do not attempt to teach or force any particular model on the reader; interpreting the contents of the book is the reader's job.